Improving the Students' Vocabulary Mastery through Youtube-based English Children Songs - Annisa Roro Kinanti Febriana; Mustasyfa Thabib Kariadi; Weksa Fradita Asriyama (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2024)
This research was conducted to improve the students’ vocabulary mastery through YouTube-based English children song. A quantitative method with a pre-experimental design was employed with the samples of 27 students at Annida Islamic elementary school. Pre-test and post-test instruments consisting 30 questions were formulated based on YouTube-English Children Songs. The results showed that the students’ vocabulary improved up to 13.4% from the mean pre-test score of 52.93 to the post-test score of 81.30. The results also showed the significance value of 0.002 < 0.05 meaning that the students’ vocabulary mastery significantly increased after using YouTube-based English Children Songs. The implementation of YouTube-based English children song was considered fairly effective (0.7 > gain > 0.3) proven by the gain score of 0.51 (medium category) obtained from the mean pre-test score of 52.93 and post-test of 81.30. Thus, the implementation of YouTube-based English children song can improve the students’ vocabulary mastery at Grade IV of Annida islamic elementary school Sokaraja and was considered effective to improve the students’ English vocabulary mastery. It is suggested that English teachers should implement YouTube-based English children songs in their teaching and learning processes and the students should practice more using YouTube-based English children songs to improve their English vocabulary mastery. Keywords: : YouTube, English Children songs, Vocabulary Mastery